STRATEGI KOMUNIKASI ACCOUNT REPRESENTATIVE KPP PRATAMA BUKITTINGGI DALAM MENSOSIALISASIKAN E-FILING UNTUK MENINGKATKAN KEPATUHAN WAJIB PAJAK - Meri Agustina (Jurnal Ilmu Komunikasi, 2019)
This study aims to determine the communication strategy of the KPP Pratama Bukittinggi Account Representative in disseminating e-filing to improve taxpayer compliance. The Directorate General of Taxes has set a strategic plan that is the migration of taxpayers to switch to using e-filing. In its implementation or implementation in the city of Bukittinggi, KPP Pratama Bukittinggi is required to succeed in the migration. This study uses a qualitative approach with descriptive methods. Data collection techniques used in this study were interviews, documentation, and literature. The informants in this study amounted to 5 (five) Account Representatives using a purposive sampling technique. The results of the study indicate that the Account Representative has a plan for implementing e-filing socialization by approaching taxpayers using language, traditions, and customs of taxpayers. Provide education counseling that the delivery of notification letters (SPT) using e-filing is easier, does not need to be in line, and is safe. The conclusion of this study shows that the KPP Pratama Bukittinggi communication strategy starts from the plan, setting message objectives, approaching the traditions and habits of taxpayers, and using the right media.